Influence of model of processed material on accuracy of forecasting of parameters of orthogonal cutting process by method of final elements - Kryvoruchko, D. V.; Zaloha, V. O.; Nekrasov, S. S. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Тhe flow stress curve influence on accuracy of orthogonal cutting of finite element simulation is studied. Technique of determination of material state equation for modelling of plasticity deformation process is suggested.